Место clupes virtutis в пропаганде единоличной власти императора Августа - Токарев, А. Н. (Давнина. Харківський історико-археологічний щорічник, 2016)
A. Tokarev. The Place Of Clupeus Virtutis In the Propaganda of the Individual Power of the Emperor AugustusThe article is devoted to the role of so-called «virtues» of clupeus aureus in the official ideology of the first Roman emperor. According to the author, Augustus did not search for a certain sample for these «virtues», but he was guided by existing circumstances. He used recent events, for example battle of Actium etc. This campaign was the response to an aspiration of some oppositional politicians to win popularity in the new conditions.Key words: Emperor Augustus, clupeus virtutis, spolia opima, M. Licinius Crassus, virtues of Emperor.